2010
DOI: 10.1017/s1461145710000313
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral benzodiazepine receptors in patients with chronic schizophrenia: a PET study with [11C]DAA1106

Abstract: Inflammatory/immunological process and glial contribution are suggested in the pathophysiology of schizophrenia. We investigated peripheral benzodiazepine receptors in brains of patients with chronic schizophrenia, which were reported to be located on mitochondria of glial cells, using [11 C]DAA1106 with positron emission tomography. Fourteen patients and 14 age-and sex-matched normal controls participated in this study. PET data were analysed by two-tissue compartment model with metabolite-corrected plasma in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(141 citation statements)
references
References 36 publications
11
126
2
2
Order By: Relevance
“…In vivo positron emission tomography (PET) imaging studies have also identified microgliosis in schizophrenia. A study of people with recent-onset schizophrenia and another study of individuals who were recovering from a psychotic episode both found increases in a marker indicative of microgliosis (binding of [ 11 C]PK11195 to the mitochondrial 18kDa translocator protein (TSPO)) in grey matter (Doorduin et al, 2009;Van Berckel et al, 2008); whereas another study of chronic patients with schizophrenia failed to find a change using another microglial marker (Takano et al, 2010) (binding of [ 11 C] DAA1106, an agonist with greater affinity for TSPO than PK11195). The latter study did find a positive correlation between microglial marker binding and positive symptoms, and thus the three in vivo PET studies are consistent with increased microgliosis being especially prominent in those with recent psychotic exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo positron emission tomography (PET) imaging studies have also identified microgliosis in schizophrenia. A study of people with recent-onset schizophrenia and another study of individuals who were recovering from a psychotic episode both found increases in a marker indicative of microgliosis (binding of [ 11 C]PK11195 to the mitochondrial 18kDa translocator protein (TSPO)) in grey matter (Doorduin et al, 2009;Van Berckel et al, 2008); whereas another study of chronic patients with schizophrenia failed to find a change using another microglial marker (Takano et al, 2010) (binding of [ 11 C] DAA1106, an agonist with greater affinity for TSPO than PK11195). The latter study did find a positive correlation between microglial marker binding and positive symptoms, and thus the three in vivo PET studies are consistent with increased microgliosis being especially prominent in those with recent psychotic exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Although [ 11 C]-(R)-PK11195 is widely used for imaging of microglia, its considerable high plasma protein binding, high levels of nonspecific binding, relatively poor blood-brain barrier permeability and short half-life, limits its use in brain imaging (Chauveau et al, 2008). Recently, alternative PET radioligands for TSPO including the phenoxyarylacetamide derivative [ 11 C]-DAA1106 and its analogues (Gulyas et al, 2009;Takano et al, 2010;Venneti et al, 2008), the imidazopyridines (PBR111) and its analogues (Boutin et al, 2007a;Fookes et al, 2008) (Boutin et al, 2007b;James et al, 2008) have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another PET study on a novel positron emission tomography (PET) ligand, [ 11 C]DAA1106, instead indicated that there were no significant microglial alterations in any of the brain regions between patients with chronic schizophrenia and control subjects. There was no significant difference between [ 11 C]DAA1106 binding of the cortical regions of normal controls and patients with schizophrenia, whereas the patients had a positive correlation between cortical [11C]DAA1106 binding and positive symptom scores [52].…”
Section: Microglial Activation In Psychiatric Disorders Based On Imagmentioning
confidence: 77%